PENGARUH CITRA MEREK DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN LAPTOP DELL DI PT BASMA WIJAYA PERKASA - afandi, khoirul; Purba, Daris (LPPM Universitas Putera Batam, 2021)
Tighter competition in the electronics industry makes various stores try to find a more appropriate strategy to sell their products. The independent variables in this study are brand image and service quality, while the dependent variable is purchasing decisions. This study aims to determine the impact of brand image and service quality on purchasing decisions. This study is a descriptive study with a quantitative approach, using primary data and secondary data, data collection techniques using a questionnaire. The population in this study is Wijaya Batam store consumers who have bought 116 laptops in the last 6 months. The sample in this study was 116 which was determined using a non-probability sampling technique with the saturated sample method. The study results are assumed to be valid and reliable, normal, do not occur multicollinearity and heteroscedasticity. The achievement of the t test shows the t test number is 10,095 > t table 1,981, brand image has a significant impact on purchasing decisions and the t test number is 2,085 > t table 1,981, service quality has a significant impact on purchasing decisions. The achievement of the F test describes the F count 62,694 > F table 3.08, brand image and service quality together have a significant impact on purchasing decisions. Keywords: Brand Image; Service Quality; and Buying Decision.